2006
DOI: 10.5194/adgeo-9-85-2006
|View full text |Cite
|
Sign up to set email alerts
|

Integration of water balance models in RIVERTWIN

Abstract: Abstract. In the project RIVERTWIN climate, hydrologic, groundwater and water quality models are integrated in order to evaluate river basin management plans established for the implementation of the EU Water Framework Directive. In such integrated models, which try to simulate all relevant processes in a river basin realistically, modelling of the water balance plays a key role. Therefore the integration of hydrological and groundwater models requires special attention. In this case study, the hydrological mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several authors used dimensionless numbers of "similarity patterns" to relate physical form to hydrological impact in basin-wide transfer functions (Berne et al, 2005;Woods, 2002;Radulovič et al, 2011). Other authors calibrated parameters of the transfer functions such as soil properties (Ali et al, 2012) or LU/LC, soil and geology (Götzinger et al, 2006) or land forms such as depressions (Baalousha et al, 2018). Simple soil water models at the basin scale for daily recharge estimates in temperate climates were used by Dripps and Bradbury (2007) and by Finch (2001) as responses to land cover changes.…”
Section: General Approach Of Process Representationmentioning
confidence: 99%
“…Several authors used dimensionless numbers of "similarity patterns" to relate physical form to hydrological impact in basin-wide transfer functions (Berne et al, 2005;Woods, 2002;Radulovič et al, 2011). Other authors calibrated parameters of the transfer functions such as soil properties (Ali et al, 2012) or LU/LC, soil and geology (Götzinger et al, 2006) or land forms such as depressions (Baalousha et al, 2018). Simple soil water models at the basin scale for daily recharge estimates in temperate climates were used by Dripps and Bradbury (2007) and by Finch (2001) as responses to land cover changes.…”
Section: General Approach Of Process Representationmentioning
confidence: 99%
“…Several authors used dimensionless numbers of 'similarity patterns' to relate physical form to hydrological impact in basin-wide transfer functions (Berne et al, 2005;Woods, 2003 andRadulovič, 2011). Other authors calibrated parameters of the transfer functions such as soil properties (Ali et al, 2012) or LU/LC, soil and geology (Götzinger, 2006). Simple soil water models at the basin scale for daily recharge estimates in moderate climates were used by Dripps et al (2007) and by Finch (2001) as responses to land cover changes.…”
Section: Regionalisation and Extrapolation Of Modelled Rc-valuesmentioning
confidence: 99%
“…Baseflow is influenced by factors such as the aquifer type, the geology and geomorphology of the catchment [4,5] and land use [4,[6][7][8][9]. Therefore, quantifying baseflow is complex: it is not commonly readily measurable [10,11], and the data quality is often poor [10]. In southern Germany, there have been very few years with above-average precipitation since 2003 [12], and studies have shown that in many regions in Germany, a decline in groundwater recharge can be expected [13].…”
Section: Introductionmentioning
confidence: 99%